Tipologi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan pada MTS.N 1 Makassar Sulawesi Selatan - Muhammad Said; Mappanganro; Masdar Masud; Andi Bunyamin; Muhammad Yusuf (Pascasarjana UMI, 2022)
Theoretically, the type of leadership has a relationship with achieving goals. This article analyzes the leadership typology applied by the Headmaster of MTs.N 1 Makassar to improve the quality of education. Before analyzing it, the data were collected through triangulation of techniques and data sources. The same data were obtained through interviews, observations, and documentation guided by the relevant research instruments. In terms of data sources, triangulation is applied by integrating data sources from informants, documents, and empirical facts observed to obtain the same data. It aims to ensure that the data presented can be trusted for its validity and accuracy. The data collected was reduced, systematized, and analyzed descriptively and qualitatively. After going through the series, the leadership type of the madrasah principle is summarized in three keywords, namely democratic, humanist, and collective types. The leadership typology is based on modern theories and the values ​​of local wisdom sitinaja, sipakatau, and sipakalebbi'. Integration between modern management theory and local wisdom can touch the sense of humanity and togetherness of madrasa stakeholders. It can support establishing a positive influence environment for all madrasa stakeholders to realize quality madrasa education services jointly. Based on that, a headmaster of madrasa must have integral intellectual, managerial, and spiritual competence and understand the values ​​of local wisdom that stakeholders uphold. The indicators for the achievement of quality improvement are assessed from several achievements and the satisfaction of various parties.